EFEK JANGKA PANJANG LATIHAN PASRAH DIRI PADA PERBAIKAN SIMPTOM DEPRESI CD4% DAN TOTAL JUMLAH LIMFOSIT - , dr. Fitria Nurul Hidayah ([Yogyakarta] : Universitas Gadjah Mada, 2014)
HIV infection and psychological illnesses had a complex relation. Someone with HIV tend to have psychological disturbances as a consequences of infection stigma or because of the brain manifestation of HIV. Depression can be used to predict decrease progression of total lymphocyte Cluster of Differentiation 4 (CD4) in patient with HIV. Latihan Pasrah Diri can be used to improve and cure depression, and there for it is supposed to be very usefull tools to help improving the immune systems. This Research aimed to determine to know the effect of long term Latihan Pasrah Diri for improving depression symptom and immune system in patient with Human Immunodeficiency Virus (HIV) The subject of this study is patient with HIV/AIDS who were hospitalized or outpatient in internal ward or Edelweis clinic. Exclution criteria was HIV at first or fourth stadium, asthma, COPD, and severe tuberculose patient. The Subject was divided into two group. First group was treated with LPD course for 63 days dan the second group was treated with original treatment. After 63 days, the patient of these two groups were re-evaluated the depression symptom and biological marker for immune system (BDI, CD4, TLC, and CD4%) This study result showed that there is significant improved of depression symptom (p value = 0,007), increased means of CD4% (p =0,014), but there is no significant improving of Total Lymphocyte Count (p value = 0,940)